2016
DOI: 10.1007/s00737-016-0615-7
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol response to the Trier Social Stress Test in pregnant women at risk for postpartum depression

Abstract: Purpose Antepartum depression and anxiety are risk factors for postpartum depression (PPD). Postpartum abnormalities in hypothalamic-pituitary-adrenal (HPA) reactivity are associated with PPD. It is not known if antepartum HPA abnormalities exist in women at risk for PPD (AR-PPD). Methods We measured salivary cortisol response to the Trier Social Stress Test (TSST) in 44 (24 AR-PPD, 20 healthy comparison) pregnant women. Depression and anxiety was measured using the Edinburgh Postnatal Depression Scale (EPDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
9
0
2
Order By: Relevance
“…The majority of the screened studies failed to meet inclusion because investigators reported on the association between maternal cortisol and infant outcomes (or between maternal depression with infant outcomes), rather than on the association between maternal cortisol and antepartum depression (N=774 out of 826, 93.7%). Table 1 provides a description of each of the 29 studies, 12 reported a statically significant association between maternal cortisol and antepartum depression (Bjelanovic et al, 2015, Diego et al, 2009, Evans et al, 2008, Field et al, 2009, Hoffman et al, 2016, Lommatzsch et al, 2006, Meliska et al, 2013, Monk et al, 2011, O’Connor et al, 2014, O’Keane et al, 2011, Peer et al, 2013, Voegtline et al, 2013) and 17 studies did not (Braithwaite et al, 2016, Davis et al, 2007, Deligiannidis et al, 2016, Glynn and Sandman, 2014, Goedhart et al, 2010, Hellgren et al, 2013, Iliadis et al, 2015, Kaasen et al, 2012, Katz et al, 2012, Luiza et al, 2015, Pedersen et al, 1993, Pluess et al, 2010, Rouse and Goodman, 2014, Salacz et al, 2012, Shea et al, 2007, Susman et al, 1999, Wikenius et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the screened studies failed to meet inclusion because investigators reported on the association between maternal cortisol and infant outcomes (or between maternal depression with infant outcomes), rather than on the association between maternal cortisol and antepartum depression (N=774 out of 826, 93.7%). Table 1 provides a description of each of the 29 studies, 12 reported a statically significant association between maternal cortisol and antepartum depression (Bjelanovic et al, 2015, Diego et al, 2009, Evans et al, 2008, Field et al, 2009, Hoffman et al, 2016, Lommatzsch et al, 2006, Meliska et al, 2013, Monk et al, 2011, O’Connor et al, 2014, O’Keane et al, 2011, Peer et al, 2013, Voegtline et al, 2013) and 17 studies did not (Braithwaite et al, 2016, Davis et al, 2007, Deligiannidis et al, 2016, Glynn and Sandman, 2014, Goedhart et al, 2010, Hellgren et al, 2013, Iliadis et al, 2015, Kaasen et al, 2012, Katz et al, 2012, Luiza et al, 2015, Pedersen et al, 1993, Pluess et al, 2010, Rouse and Goodman, 2014, Salacz et al, 2012, Shea et al, 2007, Susman et al, 1999, Wikenius et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported multiple collections of maternal cortisol throughout the pregnancy period (N=18 studies). However, such studies were predominately restricted to the second and third trimesters, and two studies reported no evidence of group by time interactions (Deligiannidis et al, 2016, Hellgren et al, 2013). No clear differences in association were observed across choice of laboratory assay or depression screener.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peripartum period is characterized by rapid and significant physiological change in plasma levels of endocrine hormones, peptides and neuroactive steroids (NAS) [123][124][125][126][127][128]. Several lines of research are actively examining the potential roles of cortisol [112,113,[129][130][131][132], corticotropin-releasing hormone (CRH) [106,[133][134][135][136], adrenocorticotropic hormone (ACTH) [137,138] oxytocin [139][140][141], prolactin [142,143], testosterone [144][145][146], NAS [121,147], and thyroid function [148][149][150][151] in PPD.…”
Section: Current Understanding Of the Neurobiology Of Postpartum Deprmentioning
confidence: 99%